Implementation of E-Commerce in Improving Business Competitiveness in the Era of the Covid-19 Pandemic - Ami Radianti; Zuhrinal M. Nawawi (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
This research focuses on the application of E-Commerce in increasing business competitiveness in the era of the Covid-19 pandemic. The purpose of this research is (1) to fnd out what E-Commerce is, (2) to find out how the implementation of E-Commerce in increasing business competitiveness in era of the Covid-19 pandemic. The research method used in this study is a descriptive qualitatively. The results of this study are the application of E-Commerce in the business world is needed by users of the latest technology such as the internet in facilitating business activities. Through the internet, business actors can easily communicate and correspond via email, chat, and others. Can produce products through advertising, introduce the company, and find new customers through the website. With the implementation of E-Commerce, it becomes market access in promoting the products it sells, increasing revenues that were previously declining to rising, helping communication between customers and sellers, and expanding the business.